2018
DOI: 10.1017/s0950268818003035
|View full text |Cite
|
Sign up to set email alerts
|

Meteorological factors and its association with hand, foot and mouth disease in Southeast and East Asia areas: a meta-analysis

Abstract: Since the late 1990s, hand, foot and mouth disease (HFMD) has become a common health problem that mostly affects children and infants in Southeast and East Asia. Global climate change is considered to be one of the major risk factors for HFMD. This study aimed to assess the correlation between meteorological factors and HFMD in the Asia-Pacific region. PubMed, Web of Science, Embase, China National Knowledge Infrastructure, Wanfang Data and Weipu Database were searched to identify relevant articles published b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 35 publications
2
13
0
Order By: Relevance
“…A nationwide HFMD outbreak in 2017 was predominantly caused by EV-A71, which predominated in many provinces of Thailand, as well as by CV-A6 and CV-A16 [ 23 ]. Numerous studies show that HFMD is related to environmental and sanitation factors such as high temperatures [ 24 ], high rainfall volumes [ 25 , 26 ], antiseptic availability, and personal hygiene [ 27 ]. In 2018, the Thai MOPH reported >70,000 cases of HFMD with three deaths [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…A nationwide HFMD outbreak in 2017 was predominantly caused by EV-A71, which predominated in many provinces of Thailand, as well as by CV-A6 and CV-A16 [ 23 ]. Numerous studies show that HFMD is related to environmental and sanitation factors such as high temperatures [ 24 ], high rainfall volumes [ 25 , 26 ], antiseptic availability, and personal hygiene [ 27 ]. In 2018, the Thai MOPH reported >70,000 cases of HFMD with three deaths [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The associations of HFMD incidence with climatic factors in Vietnam, South Korea, Japan and Hong Kong are relatively consistent: with relatively higher temperature or humidity, higher incidences are expected [12][13][14][15]. Reviews of articles including many countries also found the significant association between HFMD cases and both temperature and relative humidity [16,17], and association between HFMD cases and more climatic factors [17]. However, the conclusions of the association of incidence cyclic pattern with climatic factors in different specific locales (province, city or county) in China are inconsistent and even contradictory [18][19][20].…”
Section: Introductionmentioning
confidence: 84%
“…The annual average temperature is 16.5 − 18.0°C, the annual maximum and minimum temperatures are 35.2 − 37.4°C and −5.3 ~ −1.4°C, respectively, and the annual average precipitation is 800 − 1400 mm. According to our previous studies and a meta-analysis, these climatic features could increase the risk of HFMD [ 14 17 ].…”
Section: Methodsmentioning
confidence: 99%